Variation in coronary angiography use in Out-of-Hospital cardiac arrest. (December 2022) - Agusala, Vijay; Dale, Patrick; Khera, Rohan; Brown, Siobhan P.; Idris, Ahamed H.; Link, Mark S.; Mody, Purav
Abstract: Introduction: Multiple studies have examined the association of early coronary angiography (CAG) among out-of-hospital cardiac arrest (OHCA) patients with conflicting results. However, patterns of use of CAG among OHCA patients in real-world settings are not well-described. Methods: Utilizing data from the Resuscitation Outcomes Consortium's Continuous Chest Compressions trial for our analysis, we stratified patients based on initial arrest rhythm and ST-elevation on initial post-resuscitation electrocardiogram (ECG) and examined the rates of CAG in resuscitated patients. We also examined the rates of CAG across different trial clusters in the overall study population as well as in pre-specified patient subgroups Results: Of 26, 148 patients in the CCC trial, 5, 608 survived to hospital admission and were enrolled in the study. Among them, 26 % underwent CAG. Patients with ST-elevation underwent CAG at a significantly higher rate than patients presenting without ST-elevation (70 % vs 31 %, p < 0.001). Similarly, patients presenting with shockable rhythms underwent CAG more frequently compared with patients with non-shockable rhythms (28 % vs 5 %, p < 0.001). There was marked variation in CAG frequency across different trial clusters with the proportion of patients within a trial cluster receiving CAG ranging from 4 % − 41 %. The proportion varied more among patients with ST-elevation (16 % − 82 %) or initial shockable rhythm (11 % − 75 %) compared with no ST-elevation (2 % − 28 %) or initial non-shockable rhythm (0 % − 19 %). Conclusion: Among a national cohort of OHCA patients, large variation in the use of CAG exists, highlighting the existing uncertainty regarding perceived benefit from early CAG in OHCA.